Simulacra, Symbolic Exchange and Technology in Michel Tournier's La Goutte d'Or - David W. Price (Studies in 20th & 21st Century Literature, 1993)
In La Goutte d'Or, Michel Tournier offers a critique of Western culture by constructing a novel that reflects both Jean Baudrillard's theories of simulacra and the political economy of the sign and Martin Heidegger's meditations on technology. Tournier's novel explores the relationship between Heidegger's explanation of technology as an act of Enframing (Ge-stell) and Baudrillard's description of an economy based upon exchange-sign value. Thus, through La Goutte d 'Or, Michel Tournier depicts the violent confrontation between a symbolic exchange economy based on poietic acts and late capitalist economies of autonomized signs.
Keywords: La Goutte d& #x27; Or; Michel Tournier; Western culture; critique; Jean Baudrillard; simulacra; political economy; Martin Heidegger; technology; Heidegger; Enframing; Ge-stell; exchange-sign value; violent confrontation; violent; poietic; autonomized signs; late capitalist economies; capitalist economy